Performance of methods for detecting occlusal caries lesions: ICDAS X radiological image (Research, Society and Development, 2020)
Objective: We investigated the precision and accuracy of methods to detect caries lesions on the occlusal surface in vitro using ICDAS and radiological image. Methodology: Human third molars (n=14) were placed in an acrylic resin base and maintained wet during the study. The occlusal surfaces were visually inspected by three examiners using the International Caries Detection and Assessment System (ICDAS) method. The condition of each tooth was registered by images obtained with Digital Radiography (DR), Microcomputed Tomography (µ-CT) and Histologic Specimen (HS). For each tooth and method utilized in the study, an image was selected based on the largest extension of caries found, wherein the three examiners attributed a score to the lesion in accordance with the visual description of each method. The Kappa index, Fisher’s exact test and the Spearman´s correlation coefficient were used for evaluating reliability and accuracy, with a significance level of 5%. Results: Considerable interobserver reliability values were found for ICDAS (k = 0.701), almost perfect for µ-CT (k = 0.855) and HS (k = 0.920), and reasonable for DR (k = 0.221). Significant statistical difference was observed for ICDAS (p < 0.05), and for DR and µ-CT methods (p < 0.01). The correlation was moderate for ICDAS (r = 0.597), high for DR (r = 0.764) and perfect for µ-CT (1.000). Conclusions: the most reliability method for detecting caries lesions on occlusal surfaces in vitro was µ-CT, followed by ICDAS and DR. The most accurate method was µ-CT, followed by DR and ICDAS.